Information & Communication Technology: A Road to Hybrid Teaching & Learning Pedagogy - Kumar Singh, Anuj; Singh, Archana; ., . (International Journal of Engineering and Technology, 2018)
Nothing is permanent except change, and the past generations of human being are the evidence of this fact. Change is done for betterment of the life and for the same reason Information and Communication Technology (ICT) has evolved and entered in almost in every sector with a variety of applications. One of the most important applications of ICT is in the field of education and training, where a large number of individuals can leverage the benefits of ICT to get quality education. The main aim of this paper is to realize the need of hybrid learning methodology in current educational settings. In this paper a novel approach for hybrid teaching and learning has been presented and explained with respect to its various components.Â Â
Keywords: ICT; Hybrid; Teaching Pedagogy